Does preoperative sleep quality and distress tolerance levels in cardiovascular surgery patients affect postoperative intensive care processes? - Tulin Yildiz; Ebru Onler; Utku Durgut; Ozcan Gur; Selami Gurkan; Gunduz Yumun (National Scientific Medical Center, 2021)
Objective: This study was conducted to observe the effects of pre-operative sleep and distress intolerance levels on post-operative of cardiovascular surgery patients. Method: This is a descriptive study. The study population consisted of 120 patients who met the inclusion criteria and accepted to participate in this research.  The data were collected by using tools such as the the demographic data form which was developed by the researchers, Pittsburgh Sleep Quality Index(PSQI), Insomnia severity Index(ISI) and distress ınterolerance index(DII), and applied through face to face interviews with the patients. The multivariate analysis of variance were used in the analysis of the data. Results: This study was 120 patients, comprising 82(68.3%) males and 38(31.7%) females. According to PSQI, 77.5% of patients have a poor sleep quality. Those with good sleep quality were found to have a lower total score (37.630)>=5 poor sleep quality than the total score (31.731) of the DII. According to the PSQI, as the sleep quality decreases, the intensive care unit (ICU) stay time is increasing (23.8%, p = 0.009). Conclusion: Compared to normal population, cardiovascular surgical patients have higher levels of poor sleep quality and distressing intolerance. We found a positive correlation between impaired sleep quality and distressed intolerance levels.